Diversified exploitation of aerolysin nanopore in single‐molecule sensing and protein sequencing. Issue 4 (9th August 2020) - Lu, Si‐Min; Wu, Xue‐Yuan; Li, Meng‐Yin; Ying, Yi‐Lun; Long, Yi‐Tao
Abstract: Nanopore electrochemistry has emerged as a promising technology to achieve the real‐time investigation of nanoscale processes at the single‐molecule level in a label‐free manner. To further extend the single‐molecule sensing versatility of nanopore single‐biomolecule interface, mutant aerolysin nanopore is developed followed by exploring the sensing mechanism. The exquisite design enables the site‐directed controlling of every amino acid along the aerolysin single‐biomolecule interface with the precision of chemical group. Owing to diversified pore‐analyte weak interactions between chemical groups ( e.g ., electrostatic interactions, hydrogen bond, van der Waals' force) and steric confined effect, the mutant aerolysin displays extraordinarily high sensitivity and selectivity toward individual analytes in the stochastic sensing process. These well‐designed nanopores open more opportunities for biophysical, diagnostic applications, and even emerge as promising candidates for single‐molecule protein sequencing. Abstract : Aerolysin single‐biomolecule interface is developed to achieve single‐molecule sensing in a label‐free manner. To further enhance the sensing performance, sensing regions of aerolysin nanopore are first determined by the combination of nanopore experiments and molecular dynamics simulation. Aerolysin sensing interface is subsequently designed and tailored at the precision of chemical group via site‐directed mutagenesis. After the precisesite‐directed modification, electrochemically confined mutant aerolysin nanopore shows the excellent selectivity and sensitivity toward target single biomolecules, being further expecting to be widely applied in fast disease diagnosis and single‐molecule protein sequencing.